Deficits in reflexive covert attention following cerebellar injury - Striemer, Christopher; Cantelmi, David; Cusimano, Michael D.; Danckert, James A.; Schweizer, Tom A. (Frontiers in Human Neuroscience, 2015)
Traditionally the cerebellum has been known for its important role in coordinating motor output. Over the past fifteen years numerous studies have indicated that the cerebellum plays a role in a variety of cognitive functions including working memory, language, perceptual functions, and emotion. In addition, recent work suggests that regions of the cerebellum involved in eye movements also play a role in controlling covert visual attention. Here we investigated whether regions of the cerebellum that are not strictly tied to the control of eye movements might also contribute to covert attention. To address this question we examined the effects of circumscribed cerebellar lesions on reflexive covert attention in a group of patients (n=11) without any gross motor or oculomotor deficits, and compared their performance to a group of age-matched controls (n=11). Results indicated that the traditional RT advantage for validly cued targets was significantly smaller at the shortest (50ms) SOA for cerebellar patients compared to controls. Critically, a lesion overlap analysis indicated that this deficit in the rapid deployment of attention was linked to damage in Crus I and Crus II of the lateral cerebellum. Importantly, both cerebellar regions have connections to non-motor regions of the prefrontal and posterior parietal cortices – regions important for controlling visuospatial attention. Together, these data provide converging evidence that both lateral and midline regions of the cerebellum play an important role in the control of reflexive covert visual attention.